1987
DOI: 10.1080/00103628709367885
|View full text |Cite
|
Sign up to set email alerts
|

Micronutrient testing of plant growth media: Extractant identification and evaluation

Abstract: Using saturation extract procedures, fifteen extractants were evaluated for their ability to remove B, Fe, Mn, and Zn from a peat and vermiculite (50:50% by volume) medium amended with three levels of micronutrients. A modified saturated media extract test procedure was developed in which 30 ml of .005M DTPA was added per 100 cc of sample to be extracted. The use of this method enhanced resolution of micronutrient cation test levels in 3 media while producing only minor changes in macronutrient, pH, or soluble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

1989
1989
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 10 publications
0
35
0
Order By: Relevance
“…On the basis of the results of this experiment, it can be concluded that 0.002M DTPA used at 1 volume of medium to 1.5 volumes of extractant and a saturation extract containing DTPA (20) are equally good at predicting Fe supply to the range of plants grown. Choice between these two can be made on the basis of ease of use In routine analysis of large numbers of samples and on their relative abilities to predict available levels of other trace elements.…”
Section: Variablesmentioning
confidence: 91%
See 1 more Smart Citation
“…On the basis of the results of this experiment, it can be concluded that 0.002M DTPA used at 1 volume of medium to 1.5 volumes of extractant and a saturation extract containing DTPA (20) are equally good at predicting Fe supply to the range of plants grown. Choice between these two can be made on the basis of ease of use In routine analysis of large numbers of samples and on their relative abilities to predict available levels of other trace elements.…”
Section: Variablesmentioning
confidence: 91%
“…These samples were extracted with the Lindsay and Norvell (18) (20) were also prepared, and at harvest the media were extracted with ammonium acetate (21) as modified to 0.5M, pH 4.65, by Gabriels (22).…”
Section: Methodsmentioning
confidence: 99%
“…Phosphorus (P) was extracted using Olsen's method [9], other macronutrients and micronutrients were extracted by diethylenetriaminepentaacetic acid [10], and metals were determined by nitric acid digestion [11]. Contents were determined by inductively coupled plasma optical emission spectrometry [12] with a Spectro Genesis analyzer (SPECTRO Analytical Instruments, Kleve, Germany).…”
Section: Tissue and Soil Samplingmentioning
confidence: 99%
“…Extractable phosphorus was conducted using the modified Truog method [7], other macronutrients and micronutrients were extracted by diethylenetriaminepentaacetic acid [8], and metals were determined by nitric acid digestion [9]. Contents were determined by inductively coupled plasma optical emission spectrometry [10] with a Spectro Genesis analyzer (SPECTRO Analytical Instruments, Kleve, Germany).…”
Section: Analysesmentioning
confidence: 99%